A matter of timing: microRNA-controlled temporal identities in worms and flies - Frasch, Manfred (Genes & Development, 2008)
The first microRNAs were identified in Caenorhabditis elegans based on their functions in the temporal regulation of stage-specific cell fate decisions. Until now, it was not known whether the so-called heterochronic genes that encode miRNAs are also involved in controlling developmental transitions in other organisms. New findings by Sokol et al. (this issue of Genes & Development, pp. 1591-1596) demonstrate that the Drosophila counterpart of a heterochronic miRNA gene from C. elegans, let-7, does indeed play a role in promoting stage-specific developmental events in neuromuscular tissues during the transition from larval to adult stages, thus pointing to a more widespread utilization of miRNAs in temporal regulation of animal development.
Keywords: let-7; let-7-Complex; microRNA; heterochronic; developmental timing; neuromuscular junction